2021
DOI: 10.3390/antiox10111666
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism, Prevention, and Treatment of Radiation-Induced Salivary Gland Injury Related to Oxidative Stress

Abstract: Radiation therapy is a common treatment for head and neck cancers. However, because of the presence of nerve structures (brain stem, spinal cord, and brachial plexus), salivary glands (SGs), mucous membranes, and swallowing muscles in the head and neck regions, radiotherapy inevitably causes damage to these normal tissues. Among them, SG injury is a serious adverse event, and its clinical manifestations include changes in taste, difficulty chewing and swallowing, oral infections, and dental caries. These clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 162 publications
1
15
0
2
Order By: Relevance
“…Ionizing radiation commonly results in oxidative stress injury in salivary glands [ 24 ]. To evaluate the effects of salidroside on antioxidant defense in irradiated SMG cells, we measured the levels of MDA, CAT, and GSH as well as the activity of SOD using relevant kits.…”
Section: Resultsmentioning
confidence: 99%
“…Ionizing radiation commonly results in oxidative stress injury in salivary glands [ 24 ]. To evaluate the effects of salidroside on antioxidant defense in irradiated SMG cells, we measured the levels of MDA, CAT, and GSH as well as the activity of SOD using relevant kits.…”
Section: Resultsmentioning
confidence: 99%
“…Despite ongoing advancements in radiation technology, radiation damage to normal tissues is unavoidable ( Liu et al, 2021 ). Overcoming the side effects of radiotherapy remains a hot research topic.…”
Section: Inhibition Of Ferroptosis Can Reduce Radiation Damagementioning
confidence: 99%
“…As radiotherapy is continued, acinar cell apoptosis and acinar become atrophied and ducts dilated. At the same time, a large number of oxygen free radicals can induce cells to produce inflammatory chemokines, which further damage acinus, ducts, blood vessels and nerves 16–18 . In recent years, studies have shown that microvascular endothelial cells in salivary glands are important targets of irradiation injury 16,19 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a large number of oxygen free radicals can induce cells to produce inflammatory chemokines, which further damage acinus, ducts, blood vessels and nerves. 16 , 17 , 18 In recent years, studies have shown that microvascular endothelial cells in salivary glands are important targets of irradiation injury. 16 , 19 It is very important to explore effective methods to restore the damaged salivary gland tissue in this condition.…”
Section: Introductionmentioning
confidence: 99%